VERTEBRAL BONE MINERAL DENSITY IN ANKYLOSING SPONDYLITIS - Gülçin Kaymak Karataş; Fatma Atalay (Archives of Rheumatology, 2002)
In this study, lumbar bone mineral density (BMD) of 19 male patients with ankylosing spondylitis (AS) who were classified as mild and severe AS according to their vertebral involvement were evaluated by dual energy x-ray absorptiometry (DEXA) and quantitative computed tomography (Q-CT). Antero-posterior (AP) lumbar BMD values of mild AS patients were lower than the severe ones. Lateral L3 BMD values were higher in patients with severe AS. BMD of patients with severe AS were found to be higher than the ones with mild disease by Q-CT. There was a positive correlation between the BMD values of the L3 vertebrae measured by AP DEXA and Q-CT in patients with mild disease while a negative correlation was found in patients with severe AS. A positive correlation was found between lateral DEXA and Q-CT values in both groups. As a result; it was concluded that lateral lumbar DEXA and Q-CT techniques reflect BMD of axial skeleton correctly and both are valid methods in patients with AS.